No Germany-wide housing bubble but overvaluation in regional markets and segments - Konstantin A. Kholodilin; Claus Michelsen (DIW Economic Bulletin, 2017)
Although the housing prices in the 127 largest German cities have surged strongly in recent years, there is still no sign of a Germanywide housing bubble. In comparison with 2009, the price of condominiums has risen by around 55 percent. Single-family houses cost between 38 and 45 percent more in 2016 than seven years prior, and building lot prices have risen by around 63 percent. The study at hand shows that concerns about a national housing bubble are largely unfounded. There may, however, be bubbles on the local level -primarily in the relatively small segment of new multi-story apartment buildings but also with regard to the valuation of undeveloped residential land. Given the situation, it seems appropriate that financial regulators have opened up more policy options in order to intervene when the market trend proves unsustainable. But because the measures were diluted in the federal legislative process, the need for policy-related action remains.
Keywords: C21; C23; C53; 330; house prices; speculative bubble; explosive root; German cities